Infinitely Many Solutions for a Generalized Periodic Boundary Value Problem without the Evenness Assumption - Xiaodong Gu; Mingliang Song (Journal of Function Spaces)
In this paper, we investigate infinitely many solutions for the generalized periodic boundary value problem −x″−B0tx+B1tx=λ∇xVt,xa.e.t∈0,1,x1=Mx0,x′1=Nx′0 under the potential function Vt,x without the evenness assumption and obtain two new existence results by the multiple critical point theorem. Meanwhile, we give two corollaries for the periodic solutions of second-order Hamiltonian systems and an example that illustrates our results.